Homocysteine and other markers of cardiovascular risk during a manic episode in patients with bipolar disorder - Chiarani,Fábria (2013)
Objective: To evaluate serum levels of different biomarkers associated with cardiovascular disease in patients with bipolar disorder (BD). Patients were prospectively evaluated in two separate instances: during acute mania and after remission of manic symptoms. All measurements were compared with those of healthy controls. Methods: The study included 30 patients with BD and 30 healthy controls, matched for gender and age. Biochemical parameters evaluated included homocysteine (Hcy), folic acid, vitamin B12, ferritin, creatine kinase (CK) and C-reactive protein (CRP). Results: Hcy levels were significantly higher in the BD patients, both during mania and after achieving euthymia. When Hcy was adjusted for body mass index, there was no significant difference between patients and controls. Ferritin was the only marker that showed a significant decrease during mania when compared to both euthymic patients and controls. There were no significant differences for folate, vitamin B12, CK and CRP. Conclusions: These findings do not show an association between alterations of markers of cardiovascular risk during manic episodes. Further studies are necessary to determine factors and mechanisms associated with cardiovascular risk in patients with BD.